2013
DOI: 10.1007/978-1-62703-511-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stem Cells

Abstract: The "mesenchymal stem cells (MSCs)" are cells adherent in the bone marrow, which can be isolated to induce differentiation. In contrast to the "embryonic stem cells" whose goal is to develop a new organism, the "MSC adult stem cells" can participate in tissue growth and repair throughout postnatal life. Addition of 5-azacytidine to MSCs in vitro induces the gradual increase in cellular size and begins spontaneous beatings, thereafter differentiating into cardiomyocytes. The "Methods" and "Protocols" to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Both TGF- β 1 and 5-AZA are common inducers that are used to induce the differentiation of BMMSCs into cardiomyocyte-like cells in vitro . However, 5-AZA can cause an imbalance and affect chromatin organization at the concentration that has an inducing effect, while TGF- β 1 revealed very low efficiency [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both TGF- β 1 and 5-AZA are common inducers that are used to induce the differentiation of BMMSCs into cardiomyocyte-like cells in vitro . However, 5-AZA can cause an imbalance and affect chromatin organization at the concentration that has an inducing effect, while TGF- β 1 revealed very low efficiency [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence clearly demonstrated that BMMSCs may differentiate into cardiomyocytes in vitro and in vivo and may be home to areas of ischemic injury following the administration of BMMSCs, to provide functional recovery [ 7 ]. Many studies have shown that 5-azacytidine (5-AZA) can induce BMMSCs to differentiate into cardiomyocytes [ 8 10 ]. It is well known that transforming growth factor- β 1 (TGF- β 1) can play a similar role in the cardiac differentiation process of BMMSCs [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMMSCs have been demonstrated to be multipotent and capable of differentiating into various mesodermal and ectodermal lineages. This capability suggests their potential application in therapeutic tissue repair procedures (Malgieri et al, ; Kagami et al, ; Duong et al, ; Frenette et al, ). Additionally, compared with DPSCs, BMMSCs are easier to obtain from autologous donors.…”
Section: Introductionmentioning
confidence: 99%